Characteristics and Spectrum of Cardiotoxicity Induced by Various Antipsychotics: A Real-World Study From 2015 to 2020 Based on FAERS - He, Luyao; Yu, Yimin; Wei, Yumei; Huang, Jingjing; Shen, Yifeng; Li, Huafang (Frontiers in Pharmacology, 2022)
Objective: This study aimed to investigate characteristics and spectrum of cardiotoxicity induced by various antipsychotics based on the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database. Methods: Data of FAERS database from the first quarter of 2015 to the fourth quarter of 2020 were downloaded for disproportionality analysis. The significant signal was evaluated by reporting odds ratios and information components with statistical shrinkage transformation. Results: a total of 2361487 records were extracted for disproportionality analysis. Among the 10 antipsychotics, clozapine and amisulpride performed strong cardiotoxicity. Cardiomyopathy, cardiac arrhythmia, and de pointes/QT Prolongation were the common cardiac adverse event induced by antipsychotics. Different characteristics of the spectrum of cardiotoxicity in various APs were discovered after further data mining. And evidence of the association between antipsychotics and eosinophilic myocarditis, peripartum cardiomyopathy was provided in this study. Conclusion: Antipsychotics s presented cardiotoxicity in different degrees, and more cardiac examinations should be monitored in patients with antipsychotics.